Maternal nicotine metabolism moderates the impact of maternal cigarette smoking on infant birth weight: A Collaborative Perinatal Project investigation. (1st April 2022) - Stroud, Laura R.; Papandonatos, George D.; Jao, Nancy C.; Niaura, Raymond; Buka, Stephen; Benowitz, Neal L.
Abstract: Background: Maternal cigarette smoking is an important modifiable risk factor for low birth weight in the US. We investigated the maternal nicotine metabolite ratio (NMR; trans-3'-hydroxycotinine/cotinine) – a genetically-informed biomarker of nicotine clearance – as a moderator of links between prenatal cigarette use and birth weight. We also explored the role of race in these associations. Methods: Participants were 454 pregnant women ( M age = 25 years; 11% Black) who smoked cigarettes and their 537 infants from the Collaborative Perinatal Project. Cigarettes smoked per day were assessed at each prenatal visit; maternal NMR was assayed from third trimester serum. Birth weight was obtained from medical records. Generalized estimating equations were used to evaluate associations between cigarette smoking, NMR, race, and birth weight. Results: NMR moderated continuous associations between cigarettes per day over pregnancy and infant birth weight ( p  = .025). Among women who smoked at moderate levels (<15 cigarettes per day), those with slower NMR showed ~50–100 g decrements in birth weight versus those with faster NMR., while there were no significant associations between NMR and birth weight among women who smoked 15+ cigarettes per day. Although effects of NMR on birthweight were similar for Black and white women, Black women showed significantly slower NMR ( p  < .001). Conclusions: This is the first demonstration that the maternal nicotine metabolism phenotype moderates associations between maternal smoking during pregnancy and birth weight. Infants of women with slower nicotine metabolism – including disproportionate representation of Black women – may be at heightened risk for morbidity from maternal smoking. Highlights: Rate of nicotine metabolism moderates the impact of prenatal smoking on birth weight. In women who smoked at moderate levels, those with slower nicotine metabolism had smaller infants. Black women were more likely to have slower nicotine metabolism. Personalized interventions accounting for nicotine metabolism could be investigated.